2021
DOI: 10.1002/ldr.3825
|View full text |Cite
|
Sign up to set email alerts
|

Divergent processes and trends of desertification in Inner Mongolia and Mongolia

Abstract: Desertification and the expansion of deserts are regarded as a major threat to human livelihoods and ecosystem services, as well as achieving Sustainable Development Goals. Humans have been recognized as significant agents in the expansion of desert-like conditions, through the agency of desertification/land degradation, and through contributions to global climate change. Yet, how desertification changes and whether human or climate change drives these processes and trends over the whole Mongolia Plateau is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Some efforts have been made at smaller scales in Mongolia (Fernández-Giménez et al 2018), Inner Mongolia (Wang et al 2017, Yan et al 2020b), and Uzbekistan (Yang et al 2016). Most of these studies used either regression models or trend analysis to examine the contribution of climatic and socioeconomic drivers to vegetation dynamics (Zhang et al 2020, Guo et al 2021. In contrast, we identified the joint interactive influences between SES drivers and the seasonal effect of these drivers on ESF using SEM in Kazakhstan.…”
Section: Joint Interaction Of Seasonal Rainfall and Winter Percent Sn...mentioning
confidence: 99%
“…Some efforts have been made at smaller scales in Mongolia (Fernández-Giménez et al 2018), Inner Mongolia (Wang et al 2017, Yan et al 2020b), and Uzbekistan (Yang et al 2016). Most of these studies used either regression models or trend analysis to examine the contribution of climatic and socioeconomic drivers to vegetation dynamics (Zhang et al 2020, Guo et al 2021. In contrast, we identified the joint interactive influences between SES drivers and the seasonal effect of these drivers on ESF using SEM in Kazakhstan.…”
Section: Joint Interaction Of Seasonal Rainfall and Winter Percent Sn...mentioning
confidence: 99%
“…The desertification process is closely related to the surface vegetation condition and directly influences the regional FVC. Considering the unique climate conditions and vegetation distributions in CMREC, areas that suffered from desertification are mostly wind-eroded grassland caused by climate change and excessive logging and grazing [53,54]. According to the Land Desertification Monitoring Method GB/T20483 (http://c.gb688.cn/ bzgk/gb/showGb?type=online&hcno=62E00314AFED9EDF6BAC3562FA2AB276 (accessed on 16 December 2021)), the National Standards of PR China, we divide the desertification degree in CMREC into five categories: non-desertification, mild desertification, moderate desertification, severe desertification, and extremely severe desertification, corresponding to the FVC of more than 70%, 50-70%, 30-50%, 10-30%, and less than 10%, respectively.…”
Section: Desertification Classificationmentioning
confidence: 99%
“…Recent articles have shown that land degradation has reduced considerably during the past 20 years and that desert extent reduction is not primarily caused by a reduction in human grazing activity but rather by an increase in precipitation [112]. Guo et al (2020) reported a decrease in active desertification; however, this is mostly restricted to the more sub-humid northern part of Mongolia and the eastern parts of Inner Mongolia and does not totally affect the transitional zone between Inner Mongolia's and Mongolia's grasslands [112].…”
Section: Vegetation Response To Anthropogenic Surface Transformationmentioning
confidence: 99%
“…Recent articles have shown that land degradation has reduced considerably during the past 20 years and that desert extent reduction is not primarily caused by a reduction in human grazing activity but rather by an increase in precipitation [112]. Guo et al (2020) reported a decrease in active desertification; however, this is mostly restricted to the more sub-humid northern part of Mongolia and the eastern parts of Inner Mongolia and does not totally affect the transitional zone between Inner Mongolia's and Mongolia's grasslands [112]. Cao et al (2019;2018a;2018b) reported significantly reduced numbers of livestock in the Qinghai-Tibetan Plateau between 2001 and 2013 as a result of China's livestock reduction policy and that grazing activity cannot solely be considered the trigger of extensive grassland degradation [11].…”
Section: Vegetation Response To Anthropogenic Surface Transformationmentioning
confidence: 99%
See 1 more Smart Citation